Friendship and empire Roman diplomacy and imperialism in the Middle Republic (353-146 BC) - Burton, Paul J., 1969- (Cambridge University Press, 2011)
"The nature of roman republican international relations The history of Rome's interstate relations began, in Roman national mythology, with a striking example of the interplay between what can be loosely termed "domestic" and "international" amicitia. According to Livy, when Aeneas first arrived on Italian shores and entered the aboriginal kingdom of Latinus, the two leaders immediately established friendly relations. Latinus "by extending his right hand [to Aeneas], sanctified the good faith of the friendship that would be" (dextra data fidem futurae amicitiae sanxisse)"--